Analysis of proverbs expressing friendship in English and Uzbek languages - Nasrullaeva, Gulshan Samadovna; Jo‘rayeva, Mohidil (The Lingua Spectrum, 2026)
Friendship is one of the most significant universal human values reflected in the language and culture of every nation. Proverbs, as concise and expressive forms of folk wisdom, preserve moral principles, social norms, and cultural identity. They function as valuable linguistic units for understanding a nation’s mentality and worldview. This article examines proverbs expressing friendship in the English and Uzbek languages from a comparative linguocultural perspective. The study employs descriptive, comparative, contextual, and linguocultural methods to analyze selected proverbs related to loyalty, trust, sincerity, support, betrayal, and moral responsibility. The findings indicate that both cultures place a high value on honesty, loyalty, and mutual support in friendship. However, Uzbek proverbs tend to emphasize emotional closeness, collectivism, and moral obligation, whereas English proverbs focus more on individual reliability, practical support, and personal trustworthiness. The article contributes to the field of comparative paremiology and linguocultural studies by demonstrating how proverbs reflect both universal human values and culture-specific social attitudes.